2014
DOI: 10.4049/jimmunol.1303255
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF but Not IL-17 Is Critical for the Development of Severe Interstitial Lung Disease in SKG Mice

Abstract: Interstitial lung disease (ILD) is a common complication and sometimes a prognostic factor of connective tissue diseases (CTDs) in humans. However, suitable animal model of severe CTD-associated ILD (CTD-ILD) has been limited. In this study, we showed that zymosan-treated SKG mice developed not only arthritis but also chronic–progressive ILD with high mortality over several months. The pathological and clinical features of ILD in zymosan-treated SKG mice were similar to that of human severe CTD-ILD. ILD in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 53 publications
4
61
0
1
Order By: Relevance
“…GM-CSF genetic deletion or mAb blockade was initially found to ameliorate inflammatory arthritis and EAE (Campbell et al, 1998;Cook et al, 2001;McQualter et al, 2001;Yang and Hamilton, 2001). These strategies have subsequently been effective in inflammatory and autoimmune models, including skin inflammation (Schön et al, 2000;Samavedam et al, 2014;Scholz et al, 2017), lung inflammation and chronic obstructive pulmonary disease (Bozinovski et al, 2002;Yamashita et al, 2002;Cates et al, 2004;Vlahos et al, 2006;Shiomi et al, 2014;Nobs et al, 2019), renal injury/nephritis (Kitching et al, 2002;Timoshanko et al, 2005), peritonitis (Cook et al, 2003(Cook et al, , 2004, EAE and neuroinflammation (Ponomarev et al, 2007;Codarri et al, 2011;El-Behi et al, 2011;Ifergan et al, 2017;Sterner et al, 2019), cardiovascular disease (Shaposhnik et al, 2007;Ye et al, 2013;Hilgendorf et al, 2014;Stock et al, 2016;Wu et al, 2016;Anzai et al, 2017), colitis (Khajah et al, 2011;Griseri et al, 2015;Song et al, 2015;Kabat et al, 2016), arthritis (Greven et al, 2015;van Nieuwenhuijze et al, 2015), periodontal disease (Lam et al, 2015), dry eye disease (Dohlman et al, 2017), graftversus-host disease…”
Section: Gm-csf Administration and Targeting In Preclinical Modelsmentioning
confidence: 99%
“…GM-CSF genetic deletion or mAb blockade was initially found to ameliorate inflammatory arthritis and EAE (Campbell et al, 1998;Cook et al, 2001;McQualter et al, 2001;Yang and Hamilton, 2001). These strategies have subsequently been effective in inflammatory and autoimmune models, including skin inflammation (Schön et al, 2000;Samavedam et al, 2014;Scholz et al, 2017), lung inflammation and chronic obstructive pulmonary disease (Bozinovski et al, 2002;Yamashita et al, 2002;Cates et al, 2004;Vlahos et al, 2006;Shiomi et al, 2014;Nobs et al, 2019), renal injury/nephritis (Kitching et al, 2002;Timoshanko et al, 2005), peritonitis (Cook et al, 2003(Cook et al, , 2004, EAE and neuroinflammation (Ponomarev et al, 2007;Codarri et al, 2011;El-Behi et al, 2011;Ifergan et al, 2017;Sterner et al, 2019), cardiovascular disease (Shaposhnik et al, 2007;Ye et al, 2013;Hilgendorf et al, 2014;Stock et al, 2016;Wu et al, 2016;Anzai et al, 2017), colitis (Khajah et al, 2011;Griseri et al, 2015;Song et al, 2015;Kabat et al, 2016), arthritis (Greven et al, 2015;van Nieuwenhuijze et al, 2015), periodontal disease (Lam et al, 2015), dry eye disease (Dohlman et al, 2017), graftversus-host disease…”
Section: Gm-csf Administration and Targeting In Preclinical Modelsmentioning
confidence: 99%
“…The increase of evidence points to a central role of GM-CSF in a proinflammatory cytokine "positive feedback" loop, which often underlies the chronic nature of many inflammatory and autoimmune disorders. Th17 cells have been identified as potent inducers of many inflammatory/autoimmune diseases, including CIA, EAE, and arthritis in the SKG mouse [86,125,[140][141][142]. Th17 cells have been shown to have high "plasticity," which allows their differentiation into highly pathogenic Th1/Th17 cells (particularly in humans).…”
Section: Gm-csf In Inflammatory/autoimmune Diseasementioning
confidence: 99%
“…These cells are characterized by their coproduction of IL-17A, IFN-g, and GM-CSF, coexpression of retinoid acid receptor-related orphan receptor gt and T-bet, as well as coexpression of the Th1 and Th17 signature chemokine receptors CXCR3 and CCR6 [143][144][145]. Multiple reports have shown that it is not IL-17A but rather Th cellderived GM-CSF that mediates the pathogenic effects observed [86,142]. Accordingly, studies using GM-CSF-deficient mice have demonstrated that the inability to produce GM-CSF protects these mice from developing multiple autoimmune diseases, including: EAE, CIA, and autoimmune myocarditis [146][147][148].…”
Section: Gm-csf In Inflammatory/autoimmune Diseasementioning
confidence: 99%
“…It is, however, important to note that even in SKG.BALB/c mice, other forms of autoimmunity coexist, such as dermatitis, uveitis, ileitis and pneumonitis [20][21][22][23]. These extra-articular manifestations can vary and could easily be disrupted on a different background or in the presence of a different microflora.…”
Section: Discussionmentioning
confidence: 94%